2021
DOI: 10.1111/jog.14857
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between inflammation markers and ketonuria in hyperemesis gravidarum

Abstract: Objective: Hyperemesis gravidarum is an illness that starts in early pregnancy and manifests itself with oral intake problems, electrolyte imbalance, ketonuria, and weight loss. Inflammation is closely associated with the hyperemesis gravidarum, and inflammatory indicators have been studied to understand its pathophysiology. This study investigates the relationship of ketonuria levels with inflammatory markers platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), and neutrophil-to-lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…19 Soysal et al classified the severity of ketonuria into four groups and found a positive correlation between ketonuria levels and inflammatory markers (PLR, MLR, and NLR levels) in patients with HG. 20 In our study, NLR, PLR, and PCT counts were found to be significantly higher in the HG group than in the control group. Our results were consistent with the literature, and these hematological parameters can be considered an indicator of subclinical inflammation in patients with HG.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…19 Soysal et al classified the severity of ketonuria into four groups and found a positive correlation between ketonuria levels and inflammatory markers (PLR, MLR, and NLR levels) in patients with HG. 20 In our study, NLR, PLR, and PCT counts were found to be significantly higher in the HG group than in the control group. Our results were consistent with the literature, and these hematological parameters can be considered an indicator of subclinical inflammation in patients with HG.…”
Section: Discussionsupporting
confidence: 48%
“…Another study defined the mean corpuscular hemoglobin (MCH), NLR, and PLR levels as independent predictors of the presence of HG and level of ketone positivity 19 . Soysal et al classified the severity of ketonuria into four groups and found a positive correlation between ketonuria levels and inflammatory markers (PLR, MLR, and NLR levels) in patients with HG 20 . In our study, NLR, PLR, and PCT counts were found to be significantly higher in the HG group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Koot et al's study concluded that the level of ketonuria was not related to the severity of HEG 47 . In the study of Soysal et al, which investigated the relationship between inflammatory parameters and ketonuria levels, NLR, MLR and PLR increased significantly as the ketonuria level increased 48 . In the study of Çintesun et al, no inflammatory markers were correlated with the degree of ketonuria 36 .…”
Section: Discussionmentioning
confidence: 95%
“…47 In the study of Soysal et al, which investigated the relationship between inflammatory parameters and ketonuria levels, NLR, MLR and PLR increased significantly as the ketonuria level increased. 48 In the study of Çintesun et al, no inflammatory markers were correlated with the degree of ketonuria. 36 In this study, the level of ketonuria was not used as a criterion for HEG severity.…”
Section: T a B L E 3 Comparison Of Ketonuria And Blood Inflammation I...mentioning
confidence: 90%
“…Although most studies could not find a relationship between ketonuria and HEG severity, we detected a significant degree of ketonuria in our HEG group compared to the control group, and we observed a positive correlation between ketonuria and ADAMTS-1 levels [ 26 ]. In a different study that investigated the relation between ketonuria and HEG, Soysal et al [ 27 ] claimed that ketonuria in HEG was determined by the inflammatory response in pregnancy rather than HEG itself. Similar to that study, we found that inflammatory markers such as PDW, PCT, and MPV were higher in the HEG group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%